Association between imaging response and survival following neoadjuvant chemotherapy in patients with resectable colorectal liver metastases: A cohort study. Issue 5 (1st February 2021) - Behrenbruch, C.; Prabhakaran, S.; Udayasiri D, D.; Michael, M.; Hollande, F.; Hayes, I.; Heriot, A. G.; Knowles, B.; Thomson, B. N.
Abstract: Background: The association between the imaging response (structural or metabolic) to neoadjuvant chemotherapy (neoCT) before colorectal liver metastasis (CRLM) and survival is unclear. Method: A total of 201 patients underwent their first CRLM resection. A total of 94 (47%) patients were treated with neoCT. A multivariable, Cox proportional hazard regression analysis was performed to compare overall survival (OS) and progression‐free survival (PFS) between response groups. Results: Multivariable regression analysis of the CT/MRI ( n = 94) group showed no difference in survival (OS and PFS) in patients who had stable disease/partial response (SD/PR) or complete response (CR) versus patients who had progressive disease (PD) (OS: HR, 0.36 (95% CI: 0.11–1.19) p = .094, HR, 0.78 (95% CI: 0.13–4.50) p = .780, respectively), (PFS: HR, 0.70 (95% CI: 0.36–1.35) p = .284, HR, 0.51 (0.18–1.45) p = .203, respectively). In the FDG‐PET group ( n = 60) there was no difference in the hazard of death for patients with SD/PR or CR versus patients with PD for OS or PFS except for the PFS in the small CR subgroup (OS: HR, 0.75 (95% CI: 0.11–4.88) p = .759, HR, 1.21 (95% CI: 0.15–9.43) p = .857), (PFS: HR, 0.34% (95% CI: 0.09–1.22), p = .097, HR, 0.17 (95% CI: 0.04–0.62) p = .008, respectively). Conclusion: There was no convincing evidence of association between imaging response to neoCT and survival following CRLM resection.